2009
DOI: 10.1161/strokeaha.108.516344
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Preventable Strokes in High-Risk Patients With Atrial Fibrillation Who Are Not Adequately Anticoagulated

Abstract: Background and Purpose-Warfarin is the most effective stroke prevention medication for high-risk individuals with atrial fibrillation, yet it is often underused. This study examined the magnitude of this problem in a large contemporary, prospective stroke registry. Methods-We analyzed data from the Registry of the Canadian Stroke Network, a prospective database of consecutive patients with stroke admitted to 12 designated stroke centers in Ontario (2003Ontario ( to 2007. We included patients admitted with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
236
1
18

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(267 citation statements)
references
References 45 publications
12
236
1
18
Order By: Relevance
“…cause of concerns about bleeding, physicians tend to underdose warfarin, reducing its therapeutic efficacy. 25 Many reports document some relationship between warfarin dose and warfarin sensitivity genotype. Furthermore, there is considerable consensus in the findings among research groups from different regions ( Tables 1-5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cause of concerns about bleeding, physicians tend to underdose warfarin, reducing its therapeutic efficacy. 25 Many reports document some relationship between warfarin dose and warfarin sensitivity genotype. Furthermore, there is considerable consensus in the findings among research groups from different regions ( Tables 1-5).…”
Section: Discussionmentioning
confidence: 99%
“…Gladstone et al 25 noted that atrial fibrillation-related strokes are severe, with a 1-year mortality rate of 50%, and that warfarin anticoagulation reduces the relative risk of ischemic stroke by 65% and the risk of death by 25%. This group reported that, among patients in the Registry of the Canadian Stroke Network, only 40% had been prescribed warfarin; 30%, combined antiplatelet therapy; and 29%, no antithrombotic drug.…”
Section: Incidence Of Warfarin-related Adesmentioning
confidence: 99%
“…AF accounts for 15% of all ischemic strokes and one third of all strokes in the elderly 4. These strokes result in permanent disability in 60% of patients and death in up to 20% 5. Anticoagulation (AC) therapy is the cornerstone for stroke prevention in patients with AF.…”
Section: Introductionmentioning
confidence: 99%
“…3 Stroke registry data in Ontario showed that for up to 75% of high-risk patients with atrial fibrillation who were admitted to hospital with a stroke and who were taking warfarin at the time of admission, the international normalized ratio (INR) was subtherapeutic. 4 Direct-acting oral anticoagulants such as apixaban, which are much simpler to dose, do not require INR monitoring, and are associated with fewer drug and food interactions, have therefore become more attractive options for many clinicians and patients.…”
Section: Introductionmentioning
confidence: 99%